Registered Nurse Burnout, Job Dissatisfaction, and Missed Care in Nursing Homes - White, Elizabeth M.; Aiken, Linda H.; McHugh, Matthew D. (Journal of the American Geriatrics Society (JAGS), 2019)
OBJECTIVES To examine the relationship between registered nurse (RN) burnout, job dissatisfaction, and missed care in nursing homes. DESIGN Cross‐sectional secondary analysis of linked data from the 2015 RN4CAST‐US nurse survey and LTCfocus. SETTING A total of 540 Medicare‐ and Medicaid‐certified nursing homes in California, Florida, New Jersey, and Pennsylvania. PARTICIPANTS A total of 687 direct care RNs. MEASUREMENTS Emotional Exhaustion subscale of the Maslach Burnout Inventory, job dissatisfaction, and missed care. RESULTS Across all RNs, 30% exhibited high levels of burnout, 31% were dissatisfied with their job, and 72% reported missing one or more necessary care tasks on their last shift due to lack of time or resources. One in five RNs reported frequently being unable to complete necessary patient care. Controlling for RN and nursing home characteristics, RNs with burnout were five times more likely to leave necessary care undone (odds ratio [OR] = 4.97; 95% confidence interval [CI] = 2.56‐9.66) than RNs without burnout. RNs who were dissatisfied were 2.6 times more likely to leave necessary care undone (OR = 2.56; 95% CI = 1.68‐3.91) than RNs who were satisfied. Tasks most often left undone were comforting/talking with patients, providing adequate patient surveillance, patient/family teaching, and care planning. CONCLUSION Missed nursing care due to inadequate time or resources is common in nursing homes and is associated with RN burnout and job dissatisfaction. Improved work environments with sufficient staff hold promise for improving care and nurse retention. J Am Geriatr Soc 67:2065–2071, 2019